Household transmission of SARS-CoV-2 in a rural area in South Africa - Maimela, Gloria; Martin, C. E.; Chersich, M.; Bello, B.; Mauti, Joy; Bärnighausen, Till; Kohler, Stefan; Almuedo-Riera, A.; Luchters, S.; Sawry, S. (South African medical journal, 2024)
Background. Patterns of SARS‐CoV‐2 spread have varied by geolocation, with differences in seroprevalence between urban and rural areas, and between waves. Household spread of SARS‐CoV‐2 is a known source of new COVID‐19 infections, with rural areas in sub‐Saharan Africa being more prone than urban areas to COVID‐19 transmission because of limited access to water in some areas, delayed health‐ seeking behaviour and poor access to care. - Objectives. To explore SARS‐CoV‐2 infection incidence and transmission in rural households in South Africa (SA). - Methods. We conducted a prospective household cluster investigation between 13 April and 21 July 2021 in the Matjhabeng subdistrict, a rural area in Free State Province, SA. Adults with SARS‐CoV‐2 confirmed by polymerase chain reaction (PCR) tests (index cases, ICs) and their household contacts (HCs) were enrolled. Household visits conducted at enrolment and on days 7, 14 and 28 included interviewer‐ administered questionnaires and respiratory and blood sample collection for SARS‐CoV‐2 PCR and SARS‐CoV‐2 immunoglobulin G serological testing, respectively. Co‐primary cases were HCs with a positive SARS‐CoV‐2 PCR test at enrolment. The incidence rate (IR), using the Poisson distribution, was HCs with a new positive PCR and/or serological test per 1 000 person‐days. Associations between outcomes and HC characteristics were adjusted for intra‐cluster correlation using robust standard errors. The secondary infection rate (SIR) was the proportion of new COVID‐19 infections among susceptible HCs. - Results. Among 23 ICs and 83 HCs enrolled, 10 SARS‐CoV‐2 incident cases were identified, giving an IR of 5.8 per 1 000 person‐days (95% confidence interval (CI) 3.14 ‐ 11.95). Households with a co‐primary case had higher IRs than households without a co‐primary case (crude IR 14.16 v. 1.75, respectively; p=0.054). HIV infection, obesity and the presence of chronic conditions did not materially alter the crude IR. The SIR was 15.9% (95% CI 7.90 ‐ 29.32). Households with a lower household density (fewer household members per bedroom) had a higher IR (IR 9.58; 95% CI 4.67 ‐ 21.71) than households with a higher density (IR 3.06; 95% CI 1.00 ‐ 12.35). - Conclusion. We found a high SARS‐CoV‐2 infection rate among HCs in a rural setting, with 48% of households having a co‐primary case at the time of enrolment. Households with co‐primary cases were associated with a higher seroprevalence and incidence of SARS‐CoV‐2. Sociodemographic and health characteristics were not associated with SARS‐CoV‐2 transmission in this study, and we did not identify any transmission risks inherent to a rural setting.
Gesehen am 21.01.2025